New knowledge on the antiglycoxidative mechanism of chlorogenic acid. Issue 6 (10th June 2015) - Fernandez-Gomez, Beatriz; Ullate, Monica; Picariello, Gianluca; Ferranti, Pasquale; Mesa, Maria Dolores; del Castillo, Maria Dolores
<x xml:space="preserve">Abstract</x> Binding of CGA to protein inhibits AGE formation and provides antioxidant properties.